2022
DOI: 10.3390/ijms231911457
|View full text |Cite
|
Sign up to set email alerts
|

Novel Thieno [2,3-b]pyridine Anticancer Compound Lowers Cancer Stem Cell Fraction Inducing Shift of Lipid to Glucose Metabolism

Abstract: Due to the role of cancer stem cells (CSCs) in tumor resistance and glycosphingolipid (GSL) involvement in tumor pathogenesis, we investigated the effect of a newly synthesized compound (3-amino-N-(3-chloro-2-methylphenyl)-5-oxo-5,6,7,8-tetrahydrothieno[2,3-b]quinoline-2-carboxamide 1 on the percentage of CSCs and the expression of six GSLs on CSCs and non-CSCs on breast cancer cell lines (MDA-MB-231 and MCF-7). We also investigated the effect of 1 on the metabolic profile of these cell lines. The MTT assay wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…It has also been shown that treatment of breast cancer cells (MDA-MB-231) with a previous thieno [2,3-b]pyridine lead morphology changes and membrane blebbing that mimics PI-PLC knockdown cells [4]. It has also been shown that treatment of breast cancer cells (MDA-MB-231) with a previous thieno [2,3-b]pyridine lead compound induced growth reduction in addition to causing cells to shift from lipid to glucose metabolism, providing further evidence that these compounds act through inferring with lipid metabolism [2]. Additional studies into thienopyridine-containing compounds have identified a range of other potential cellular targets, including TDP-1 [5], P2Y12 receptors [6], Adenosine A2A receptors [7], as well as potentially inhibiting microtubule assembly [8,9].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…It has also been shown that treatment of breast cancer cells (MDA-MB-231) with a previous thieno [2,3-b]pyridine lead morphology changes and membrane blebbing that mimics PI-PLC knockdown cells [4]. It has also been shown that treatment of breast cancer cells (MDA-MB-231) with a previous thieno [2,3-b]pyridine lead compound induced growth reduction in addition to causing cells to shift from lipid to glucose metabolism, providing further evidence that these compounds act through inferring with lipid metabolism [2]. Additional studies into thienopyridine-containing compounds have identified a range of other potential cellular targets, including TDP-1 [5], P2Y12 receptors [6], Adenosine A2A receptors [7], as well as potentially inhibiting microtubule assembly [8,9].…”
Section: Introductionmentioning
confidence: 85%
“…The 3-amino-2-arylcarboxamido-thieno [2,3-b]pyridines are a family of drug-like molecules that are well established in the literature for inducing potent anti-proliferative effects in triple-negative breast cancer (MDA-MB-231) and colorectal cancer (HCT116) pcell lines [1][2][3][4]. It is postulated that thieno [2,3-b]pyridines induce anti-neoplastic action through disrupting phospholipid metabolism by the inhibition of phosphoinositide phospholipase C (PI-PLC).…”
Section: Introductionmentioning
confidence: 99%
“…Thieno­[2,3- b ]­pyridine derivatives occupy a unique position and have received considerable attention due to their diverse pharmacological activities, which include anticancer, , antiviral, , anti-inflammatory, , antimicrobial, , antidiabetic, , and osteogenic antiproliferative activity. Furthermore, they can be used as adenosine A1 receptor ligands for the potential treatment of epilepsy and as antiplatelet drugs .…”
Section: Introductionmentioning
confidence: 99%
“…Pyridine derivatives a heterocyclic compound that have a wide range of biological activities [1][2][3][4], including antimicrobial [5,6], antitumor [7,8], antiviral [9], anticancer [10], antituberculosis, anti-inflammatory [11] [12], and heart treatment properties [13,14]. Sulfonamides have also shown strong pharmacological effects [14].…”
Section: Introductionmentioning
confidence: 99%